PERLINDUNGAN HUKUM TERHADAP TERTANGGUNG DALAM HAL PENANGGUNG MENOLAK KLAIM ASURANSI AKIBAT TERJADINYA RESIKO TOTAL LOSS ONLY (STUDI PUTUSAN PENGADILAN NEGERI MEDAN NO. 392/PDT.G/2013/PN.MDN) - ANDRIANSYAH PUTRA NAPITUPULU (PREMISE LAW JURNAL, 2017)
This research discussed legal protection for the insured because the insurer refused the claim when the ‘total loss only’ (TLO) occurred by using the Medan District Court’s Verdict No 392/Pdt.G/2013/PN.Mdn) as the material of the analysis. The term, loss in not only used as the loss of insured vehicles because of criminal act, but also damage. The damaged insured by TLO is at least 75% which is intentional since it s certain that the vehicle is thoroughly damaged and cannot be used anymore. As the means of mobility, it cannot be functioned although it still exists. The research used juridical normative of legal doctrinaire research which was referred to legal norms by using statue approach and legal provisions, especial law on insurance. Keywords: Legal Protection, the Insured, Risk for Claim, Total Loss Only